Situation and Development of Vocational Education and Training (VET) and VET Science in Namibia - Subasubani, J. Kamwi [Verfasser] (My University, 2017)
"Ever since independence, Namibia has invested heavily in Education and Training. However, the Education and Training system has remained weak by international standards, and therefore requires significant interventions of which teacher/VET Trainer is central. The provision of Vocational Education and Training (VET) is a challenge, worsened by the inaccurate perception that VET is second-rate alternative to a purely academic education. Thus, there is an urgent need to raise the quality of VET in order to improve the quality of VET graduates who are skilled, employable and ready to contribute to the development agenda. The NTA has identified the major factors that prevent VET from fulfilling its mandate in the developmental agenda, leading to decisive measures been taken, such as: improving the VET Curricula, availing up-to-date training equipment and materials, and most importantly the Training of Trainers (ToT). Different studies have been conducted to establish the competency levels of VET Trainers, and results shown major deficiencies that requires an urgent need for up-skilling and capacity building of trainers. The need to up-skill and capacitate VET trainers has resulted in a ToT system being developed. Immediate actions have been taken and cooperation with support initiatives have been strengthened. The major problem faced by NTA is the development of a sustainable Education and Training system including technical, pedagogical and workplace (industry) exposure of VET trainers. Best practice models have to be established which show strengths, weaknesses and opportunities of the approach. The objectives of this paper are to explain the current the VET trainer education and training system and to present the ToT system challenges on the way to a full-fledged nationwide system." (author's abstract; BIBB-Doku)
Keywords: S System beruflicher Bildung; P 3.2.1 Ausbilder; I 2.3.1 Afrika; Berufsbildungssystem; Ausbilder; Ausbilderqualifizierung; Namibia